2022
DOI: 10.3389/fimmu.2022.993622
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab plus ipilimumab induced endocrinopathy and acute interstitial nephritis in metastatic sarcomatoid renal-cell carcinoma: A case report and review of literature

Abstract: The prognosis of sarcomatoid renal cell carcinoma has changed dramatically with the emergence of immune checkpoint inhibitors. Notably the use of nivolumab and ipilimumab combination therapy has demonstrated promising durable therapeutic response for patients with treatment-naïve sarcomatoid renal-cell carcinoma. We present a case of 45-year-old man with a history of metastatic sarcomatoid renal cell carcinoma treated with nivolumab plus ipilimumab who developed type 1 diabetes mellitus, adrenal insufficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Further heterogeneity was difficult to assess in our study because some of the associated factors were not reported in the original articles. With an increasing appearance of new studies [ 51 , 52 , 53 ], our understanding of ICI-kidney IRAEs will be deepened gradually. Further studies are needed to explore the related mechanism and help better manage the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further heterogeneity was difficult to assess in our study because some of the associated factors were not reported in the original articles. With an increasing appearance of new studies [ 51 , 52 , 53 ], our understanding of ICI-kidney IRAEs will be deepened gradually. Further studies are needed to explore the related mechanism and help better manage the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Three irAEs, such as thyroid disease, diabetes mellitus, and hypophysitis, developed in this case. In 7 previous reports of triple endocrine irAEs due to ICI therapy (Table 4), [21–27] thyroid disease and/or T1D mellitus developed before onset of hypophysitis. In 3 cases, ICI therapies were continued or reinitiated after resolution of irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 shows cases reporting hypophysitis and T1D. [3,[21][22][23][24][25][26][27][28][29][30][31][32] ICIs are anti-PD-1 monotherapy, anti-PD-L1 monotherapy, and combination therapy of anti-PD-1/anti-PD-L1 and anti-CTLA-4. No cases with hypophysitis and T1D due to ipilimumab monotherapy were reported.…”
Section: Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…ICIs besides their direct effect on adrenals, have been also associated with hypophysitis with an incidence of up to 17% of the cases [23–29,30 ▪▪ ]. Its prevalence generally depends on the dosage and specific drug class (anti-CTLA-4, anti-PD-1 or anti-PD-L1) [30 ▪▪ ,31].…”
Section: Causes Of Adrenal Insufficiencymentioning
confidence: 99%